Analisis Tingkat Kepuasan Pengguna Terhadap Layanan Transportasi Online (Grab) Studi Kasus Stasiun Kota Tegal - Rizal Aprianto; Finata Dwi Putri; Syafriyanto, Rui Hanan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
In the digital era, advancements in transportation services are increasing, including the presence of online motorcycle taxis such as Grab as a form of technological innovation. One of the services that is growing rapidly in Indonesia is Grab. This study aims to assess the level of satisfaction of Grab application users in the Tegal City Station area. The approach applied in this study is quantitative, with the Naive Bayes algorithm used as the data analysis technique. Naive Bayes is a classification method based on the principles of probability and statistics, which is effective in processing text data. Data were collected through the distribution of online questionnaires to 98 respondents who are active users of the online motorcycle taxi application (Grab) at Tegal City Station. The variables measured include perceived usefulness (Perceived Usefulness), perceived ease of use (Perceived Ease of Use), and user satisfaction level. The results of this study indicate that the majority of respondents are satisfied with Grab services, especially in terms of the application's ease of use. Thus, it can be concluded that the Grab application is able to provide a positive experience for users at Tegal City Station.